Azure DevOps for Beginners. - Ritscher, Walt; Labs, Learn-it (linkedin.com, 2024)
Learn everything you need to get up and running with the Azure DevOps bundle of services. This course covers Azure Boards, Azure Repos, Azure Pipelines, and ways to extend DevOps.